Pengaruh Pelatihan, Pengembangan Karir dan Motivasi terhadap Kinerja Karyawan PT Surteckariya Indonesia Bagian Produksi - Febri Yunian Bramasta; Sri Wahyuningsih (Journal on Education, 2023)
This research was conducted with the aim to determine the effect of training, career development and motivation on the performance of employees of PT. Surteckariya Indonesia production department. The population in this study are employees of PT. Surteckariya Indonesia is part of the production team, with a total of 80 employees. The sampling technique in this study used a saturated sample technique, namely a sampling technique using the entire population as a sample. Thus the number of samples in this study were 80 people. The data analysis technique used is multiple linear regression analysis. The test results show that training has no positive effect on employee performance, career development has a positive effect on employee performance, motivation has a positive effect on employee performance at PT. Surteckariya Indonesia production department.